2012
DOI: 10.1039/c2jm33654e
|View full text |Cite
|
Sign up to set email alerts
|

Low-power photon upconversion through triplet–triplet annihilation in polymers

Abstract: Low-power upconversion via sensitized triplet-triplet annihilation (TTA-UC) is a useful and versatile process that allows for the conversion of optical radiation into photons of higher energy. While this effect had been known to occur in solution for some 50 years, it was only very recently realized for the first time in polymers. The possibility to realize the TTA-UC process in solid materials is important for a variety of applications that range from the optimization of photovoltaic devices to bioimaging. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
412
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 395 publications
(416 citation statements)
references
References 114 publications
0
412
0
1
Order By: Relevance
“…140 Recent studies imply that this indeed increases the UC yield in liquid solutions, 141 while earlier studies have found an increase of the TTA photon yield of a porphyrin sensitizer end-capped poly-pentaphenylene solid TTA emitter 142 as compared to a porphyrin-doped host. Although others have argued that the gain in UC efficiency in this system was minute and relate this finding to a possible exciton back-diffusion, 58 these strategies point in the right direction but require much more effort in order to realize efficient and robust TTA systems tailored for solar energy applications.…”
Section: Increasing the Molecular Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…140 Recent studies imply that this indeed increases the UC yield in liquid solutions, 141 while earlier studies have found an increase of the TTA photon yield of a porphyrin sensitizer end-capped poly-pentaphenylene solid TTA emitter 142 as compared to a porphyrin-doped host. Although others have argued that the gain in UC efficiency in this system was minute and relate this finding to a possible exciton back-diffusion, 58 these strategies point in the right direction but require much more effort in order to realize efficient and robust TTA systems tailored for solar energy applications.…”
Section: Increasing the Molecular Densitymentioning
confidence: 99%
“…The reader is referred to the review article of Simon and Weder, who discuss the pending issues in great detail. 58 Strategies that might allow such control will be discussed below in Section 4.2.3.…”
Section: Towards Solid-state Ttamentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10] In the typical TTA-UC process, (1) a triplet excited state of the donor is formed by intersystem crossing (ISC) from a photoexcited singlet state, (2) acceptor triplet excited states are populated by triplet energy transfer (TET) from the donor triplets, and (3) annihilation between two acceptor triplets (TTA) generates an acceptor singlet excited state, from which upconverted delayed fluorescence is emitted [ Fig. 1(a)].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] In PUC, the material or chemical composition is irradiated at a longer wavelength than the ensuing (delayed) fluorescence. As such, it has potential applications in areas including: Photovoltaics, in recovering below-bandgap photon losses; [6][7][8][9][10] Photoelectrochemistry, similarly generating more usable photons; [11][12][13] Biological Imaging, in circumventing autofluorescence; [14][15][16][17] Drug Activation, stimulating drug release inside the body through the tissue window; 18,19 and Water Purification, generating short wavelengths to degrade water impurites.…”
Section: Introductionmentioning
confidence: 99%